Functional autoantibodies against G protein-coupled receptors in hepatic and pulmonary hypertensions in human schistosomiasis - Botoni, Fernando Antonio; Lambertucci, José Roberto; Santos, Robson Augusto Souza; Müller, Johannes; Talvani, Andre; Wallukat, Gerd (Frontiers in Immunology, 2024)
Introduction Schistosomiasis (SM) is a parasitic disease caused by Schistosoma mansoni. SM causes chronic inflammation induced by parasitic eggs, with collagen/fibrosis deposition in the granuloma process in the liver, spleen, central nervous system, kidneys, and lungs. Pulmonary arterial hypertension (PAH) is a clinical manifestation characterized by high pressure in the pulmonary circulation and right ventricular overload. This study investigated the production of functional autoantibodies (fAABs) against the second loop of the G-protein-coupled receptor (GPCR) in the presence of hepatic and PAH forms of human SM. Methods Uninfected and infected individuals presenting acute and chronic manifestations (e.g., hepatointestinal, hepato-splenic without PAH, and hepato-splenic with PAH) of SM were clinically evaluated and their blood was collected to identify fAABs/GPCRs capable of recognizing endothelin 1, angiotensin II, and a-1 adrenergic receptor. Human serum was analyzed in rat cardiomyocytes cultured in the presence of the receptor antagonists urapidil, losartan, and BQ123. Results The fAABs/GPCRs from chronic hepatic and PAH SM individuals, but not from acute SM individuals, recognized the three receptors. In the presence of the antagonists, there was a reduction in beating rate changes in cultured cardiomyocytes. In addition, binding sites on the extracellular domain functionality of fAABs were identified, and IgG1 and/or IgG3 antibodies were found to be related to fAABs. Conclusion Our data suggest that fAABs against GPCR play an essential role in vascular activity in chronic SM (hepatic and PAH) and might be involved in the development of hypertensive forms of SM.